Modulation of Intermuscular Beta Coherence in Different Rhythmic Mandibular Behaviors - Usler, Evan R.; Wei, Xiaomei; Simione, Meg; Richburg, Brian; Stipancic, Kaila L.; Green, Jordan R. (Frontiers in Human Neuroscience, 2020)
Introduction: Jaw movement during chewing and speech is facilitated by neural activation patterns for opening and closing movements of the mandible. This study investigated anatomic- and task-dependent differences in intermuscular coherence (IMC) and their association with parameters of jaw muscle activity using surface electromyography (EMG). Methods: We recorded EMG activation from bilateral and ipsilateral jaw-closing muscle pairs during non-nutritive and nutritive chewing, and during a syllable repetition task. IMC and cross-correlational analyses between bilateral and ipsilateral muscle pairs were performed. Results: IMC in the beta band was statistically significant between agonist jaw-closing muscle pairs, with beta IMC weaker for rapid syllable repetition compared to chewing tasks. Cross-correlational analysis of muscle co-activation, as well as EMG burst amplitude, were positively associated with beta IMC strength. Discussion: Beta IMC was influenced heavily by task-dependent behavioral goals and physiologic demands, which was interpreted as evidence of shared neural drive among jaw-closing muscles.